Flavour and CP predictions from orbifold compactification - Francisco J. de Anda; José W.F. Valle; Carlos A. Vaquera-Araujo (Physics Letters B, 2020)
We propose a theory for fermion masses and mixings in which an A4 family symmetry arises naturally from a six-dimensional spacetime after orbifold compactification. The flavour symmetry leads to the successful “golden” quark-lepton unification formula. The model reproduces oscillation parameters with good precision, giving sharp predictions for the CP violating phases of quarks and leptons, in particular δℓ≃+268∘. The effective neutrinoless double-beta decay mass parameter is also sharply predicted as 〈mββ〉≃2.65meV.